2001
DOI: 10.1021/jp010089a
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Transition Temperature of 2H−TaS2 Intercalation Compounds Determined by the Phonon Spectrum

Abstract: The specific heat in the normal and superconducting states of single-crystal intercalation compounds of the host material 2H-TaS 2 was measured from 1.7 to 9 K by use of a thermal relaxation method. By studying two extreme cases of charge transfer n, namely the 9 Å methylene blue intercalation compound (9 Å MB + -TaS 2 ) (n ) 0.06) and K 0.33 TaS 2 (n ) 0.33), and comparing the results with literature data, it is seen that charge transfer has only minor influence on the electronic specific heat in the normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…A traditional way for fabricating intercalated layered dichalcogend compounds consists of two steps, the first step is to prepare poly-crystalline compound or single crystal of M X 2 by chemical reaction or iodine-transport reaction 7,20 ; Secondly, the intercalation is carried out by chemical treatments, the samples are dipped into concentrated solutions containing the intercalated atoms 7,16,20 , or exposed to metal vapors in a closed ampoule 16 . A new method suited for preparing samples for the studies of surface science was also reported, the intercalated compounds were prepared by in situ evaporation of metal atoms to the (0 0 0 1) cleaved surface of the TMDC's crystals.…”
Section: Methodsmentioning
confidence: 99%
“…A traditional way for fabricating intercalated layered dichalcogend compounds consists of two steps, the first step is to prepare poly-crystalline compound or single crystal of M X 2 by chemical reaction or iodine-transport reaction 7,20 ; Secondly, the intercalation is carried out by chemical treatments, the samples are dipped into concentrated solutions containing the intercalated atoms 7,16,20 , or exposed to metal vapors in a closed ampoule 16 . A new method suited for preparing samples for the studies of surface science was also reported, the intercalated compounds were prepared by in situ evaporation of metal atoms to the (0 0 0 1) cleaved surface of the TMDC's crystals.…”
Section: Methodsmentioning
confidence: 99%
“…[19] The nanowires exhibit superconductivity, with an onset temperature of 3.4 K (Figure 4). This behavior is in stark contrast with that of bulk 2H-TaS 2 , which exhibits superconductivity below 1 K (T c = 0.6 [14] or 0.8 K [20] ). Further, the transition temperature of the 2H-TaS 2 nanowires is higher than that reported for the 6R-TaS 2 nanobelts (T c = 2.7 K).…”
mentioning
confidence: 88%
“…Another class of TMD intercalation compounds is the hydrates with transition metal ions as intercalants into 2H-TaS 2 [138][139][140][141][142][143][144][145]. These compounds have the general composition M x (H 2 O) y T χ 2 , where T can be either Ta or Nb, χ = S, and M can be an alkali or a rare earth ion.…”
Section: Intercalated Transition Metal Dichalcogenidesmentioning
confidence: 99%